Further Validation of Measures of Target Detection and Stereotype Activation in the Stereotype Misperception Task - Reichardt, Regina; Rivers, Andrew M.; Reichardt, Joerg; Sherman, Jeffrey W. (Frontiers in Psychology, 2020)
Previous research presented a multinomial model to estimate four latent processes (target detection, stereotype activation, stereotype application, guessing) that contribute to responses in the Stereotype Misperception Task, an indirect measure of stereotyping (Krieglmeyer & Sherman, 2012). The present research further investigates the validity of the target detection (D) and stereotype activation (SAC) parameters. To this end, the data from Experiment 2 and Experiment 4 in Krieglmeyer and Sherman (2012) were re-analyzed using a bootstrap method to investigate the robustness of the results. Furthermore, two conceptual replication studies were conducted and analyzed with the same bootstrap method. A manipulation of target distinctness influenced the D parameter as predicted. A manipulation of prime prototypicality influenced the SAC parameter as predicted. Taken together, the results support the validity of the D and SAC model parameters.